Nollywood as a Repository of Yoruba Historical and Cultural Identity: A Study of Tunde Kelani’s Ti Oluwa Ni Ile - AUDU, Jamiu Kolawole; TAIWO, Ajibola Oluwakemi; BELLO, Mistura Eniola (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This paper examined the intricate relationship between historical culture, Nollywood (with specific reference to the Yoruba movie industry), and Yoruba identity. It explored how Yoruba films serve as repositories of Yoruba cultural heritage, language, and traditions. Specifically, this study analyses Tunde Kelani’s 1991 movie Ti Oluwa Ni Ile to provide insight into Yoruba life and worldviews as reflected through cinema. The research discusses the film’s portrayal of Yoruba customs, traditions, language, and elements of mythology, while also addressing the criticisms and challenges surrounding cultural representation in Nollywood. Using a qualitative approach anchored in historical analysis, the study interpreted how Ti Oluwa Ni Ile functions as an archive of Yoruba values such as respect for elders, integrity, and the virtue of hard work—principles that define Yoruba identity. The paper concluded by emphasizing the film’s significance to younger generations in an increasingly globalized world. For many, it offers a lens through which to reconnect with their cultural past and better understand the moral and communal values that underpin Yoruba life.